Field Observations and Physical‐Biogeochemical Modeling Suggest Low Silicon Affinity for Antarctic Fast Ice Diatoms. Issue 11 (17th November 2019) - Lim, S. M.; Moreau, S.; Vancoppenolle, M.; Deman, F.; Roukaerts, A.; Meiners, K. M.; Janssens, J.; Lannuzel, D.
Abstract: We use field observations from late spring and a one‐dimensional sea‐ice model to explore a high nutrient, high chlorophyll system in Antarctic land‐fast ice. Lack of variability in chlorophyll a concentration and organic carbon content over the 17‐day sampling period suggests a balance between macronutrient sources and biological uptake. Nitrate, nitrite, phosphate, and ammonium were measured at concentrations well above salinity‐predicted levels, indicating nutrient accumulation fueled by remineralization processes. However, silicic acid (DSi) was depleted relative to seawater and was potentially limiting. One‐dimensional physical‐biogeochemical sea‐ice model simulations at the observation site achieve extremely high algal growth and DSi uptake with a DSi half‐saturation constant used for pelagic diatoms (KSi = 3.9 μM) and are not sufficiently improved by tuning the DSi:carbon ratio or DSi remineralization rate. In contrast, diatom biomass in the bottom ice, which makes up 70% of the observed chlorophyll, is simulated using KSi an order of magnitude higher (50 μM), a value similar to that measured in a few Antarctic diatom cultures. Some sea‐ice diatoms may therefore experience limitation at relatively high ambient DSi concentrations compared to pelagic diatoms. Our study highlights the urgent need for observational data on sea‐ice algal affinity for DSi to further support this hypothesis. A lower algal growth rate increases model predictions of DSi in the upper sea ice to more accurate concentrations. The model currently does not account for the non‐diatom communities that dominate those layers, and thus, modeling diatom communities overpredicts DSi uptake in the upper ice. Plain Language Summary: Microscopic, single‐celled algae growing inside Antarctic sea ice play a small, but important, role in the carbon cycle of polar oceans. These algae use photosynthesis to convert carbon dioxide to organic carbon and are an important food source for larger organisms. The growth of sea‐ice algae is partly controlled by their uptake of essential nutrients under favorable light conditions. Therefore, a better understanding of nutrients in sea ice can improve ecosystem models. We studied two weeks of measurements of coastal sea‐ice characteristics in late spring at a site in East Antarctica. There were high amounts of both algae and nutrients, indicating recycling processes that return nutrients to the sea ice, even as algae consume nutrients. Sticky biofilms may also prevent nutrients from being removed by seawater. We then tested a sea‐ice model to see if it matched our field measurements. We had to adjust how readily algal cells in the model take up silicon—a nutrient used to build diatoms' (the dominant algal group) walls—from their environment to obtain a close match. Previously used values were taken from experiments with non‐ice associated marine algae, so better estimates specific to sea‐ice algae are needed to accurately include sea‐ice processes in large‐scale models. Key Points: We observed high chlorophyll a and macronutrient concentrations co‐occurring at the bottom of Antarctic land‐fast sea ice in late spring Remineralization processes and adsorption within sea ice best explain the required sources of nitrate and nitrite, phosphate, and ammonium Biogeochemical modeling suggests that sea‐ice diatoms have a lower affinity for silicic acid than pelagic diatoms